Outcome of ultrasonographic imaging in infants with sacral dimple - Jin Hyuk Choi; Taekwan Lee; Hyeok Hee Kwon; Sun Kyoung You; Joon Won Kang (Korean Pediatric Society, 2018)
PurposeSacral dimples are a common cutaneous anomaly in infants. Spine ultrasonography (USG) is an effective and safe screening tool for patients with a sacral dimple. The aim of this study was to determine the clinical manifestations in patients with an isolated sacral dimple and to review the management of spinal cord abnormalities identified with USG.MethodsWe reviewed clinical records and collected data on admissions for a sacral dimple from March 2014 through February 2017 that were evaluated with spine USG by a pediatric radiologist. During the same period, patients who were admitted for other complaints, but were found to have a sacral dimple were also included.ResultsThis study included 230 infants under 6-months-old (130 males and 100 females; mean age 52.8±42.6 days). Thirty-one infants with a sacral dimple had an echogenic filum terminale, and 57 children had a filar cyst. Twenty-seven patients had a low-lying spinal cord, and only one patient was suspected of having a tethered cord. Follow-up spine USG was performed in 28 patients, which showed normalization or insignificant change.ConclusionIn this study, all but one infant with a sacral dimple had benign imaging findings. USG can be recommended in infants with a sacral dimple for its convenience and safety.